2014
DOI: 10.1039/c4ob00496e
|View full text |Cite
|
Sign up to set email alerts
|

Studies on the stereochemical assignment of 3-acylidene 2-oxindoles

Abstract: The designation of E/Z-geometrical isomers in 3-acylidene 2-oxindoles by NMR spectroscopy can lead to erroneous assignment of alkene stereochemistry because of the narrow chemical shift range observed over a large series of analogues. In contrast, UV-Vis spectroscopy offers a convenient and more reliable method for alkene stereochemical assignment. A combination of X-ray crystallography and theoretical studies shows that the observed differences in UV-Vis spectroscopic behaviour relate to the twisted conformat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
17
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 29 publications
(18 citation statements)
references
References 16 publications
1
17
0
Order By: Relevance
“…In addition, the IR data exhibited absorption bands at 3395 (NH) and 1712, 1662 (2C]O). According to previous reports, 33,34 H-4 (d H 8.31 ppm) and H-8 (d H 7.45 ppm) chemical shis suggest the E conguration at C-3/C-8 double bond. Furthermore, both E and Z conformers' energies were minimized and the distance between H-4, H-10, H-13 and H-14 were determined that were found to be less than 5 A in E form and more in Z form, from this points the presence of 1 H-1 H NOESY correlations (crosspeaks) between H-4 and H-10, H-13 and H-14 together with their absence between H-4 and H-8 (Fig.…”
Section: Chemistrysupporting
confidence: 53%
“…In addition, the IR data exhibited absorption bands at 3395 (NH) and 1712, 1662 (2C]O). According to previous reports, 33,34 H-4 (d H 8.31 ppm) and H-8 (d H 7.45 ppm) chemical shis suggest the E conguration at C-3/C-8 double bond. Furthermore, both E and Z conformers' energies were minimized and the distance between H-4, H-10, H-13 and H-14 were determined that were found to be less than 5 A in E form and more in Z form, from this points the presence of 1 H-1 H NOESY correlations (crosspeaks) between H-4 and H-10, H-13 and H-14 together with their absence between H-4 and H-8 (Fig.…”
Section: Chemistrysupporting
confidence: 53%
“…It was observed that the arylative Meyer–Schuster rearrangement of heterocycle‐containing tertiary alkynols was equally efficient (Scheme ). For instance, the relevant13 3‐acylidene‐2‐oxindole derivative 7a could be smoothly afforded in reasonable yield and with total Z diastereoselectivity starting from 3‐ethynyl‐3‐hydroxyindolin‐2‐one 6a (Scheme ) 14. Curiously, adducts 7b and 7c , initially obtained as their corresponding hemiacetals by 1,2‐addition reaction of methanol to the α,β‐unsaturated ketone moiety, evolves through protonation, dehydration, and final hydration to oxindole‐tethered tetrasubstituted olefins 8b and 8c .…”
Section: Methodsmentioning
confidence: 99%
“…Notably, this latter class of compounds has been shown to undergo bio-reduction in red blood cells thereby exhibiting potent antiplasmodial activity. 10 Finally, in relation to our recent interest in the synthesis and spectroscopic properties of 3-acylidene 2-oxindoles, 11 our observation that displacement of the iodide could be quite facile (Scheme 4, Eq (3)) suggested that 2-iodoisatogens could in fact offer a facile strategy for the synthesis of the isomeric 2-acylidene 3-oxindoles. These compounds are relatively rare and have been far less studied with respect to their biological activity or cycloaddition chemistry as compared to the 2oxindole isomers.…”
Section: Scheme 3 Cyclization Of Electron Deficient Substratesmentioning
confidence: 91%